Comparison of atomic-force microscopy methods during the study of amorphous carbon films - Nemkayeva, R.R.; Mukhametkarimov, Y.S.; Alpysbayeva, B.Ye. (Recent Contributions to Physics, 2018)
The paper presents study results of amorphous carbon film using atomic-force microscopy. Principles of main measuring techniques and parameters, determining lateral resolution and resolution by z axis, as well as special features of different tips are considered. Comparison and application peculiarities are performed for semicontact and contact modes when study soft films with low adhesion. It is shown, that choosing scanning method of atomic-force microscopy it is always required to take many factors into consideration – firstly, the sample peculiarities and information to be obtained as a result of measurements. In case of sufficiently hard sample and necessity to perform precise measurements, it is recommended to use soft probe with long cantilever in contact mode. In case of “difficult” samples – soft, with extended surface and low adhesion, semicontact mode is used. Method for measurement of film’s thickness is considered and analysis of accuracy depending on measuring mode is performed. Error of measurement of thickness using semicontact probe in contact mode averaged 15 nm. At the same time, semicontact mode allows to obtain fine image without surface damages and correctly assess the depth of a scratch.